PENINGKATAN KEMAMPUAN ANAK USIA DINI MENGENAL LAMBANG BILANGAN MELALUI MEDIA PLAYDOUGH - Sumardi, Sumardi; Rahman, Taopik; Gustini, Iis Syifa (JURNAL PAUD AGAPEDIA, 2017)
This research aimed to improve the ability to recognize the symbol of number with playdough in Group A TK WijayaKusumah / Kartika XIX-26 Tawang District Tasikmalaya.This research was a classroom action research using Kemmis and Taggart model which was implemented in 3 cycles. The subjects of this study were 12 children of group A. Data collection techniques in this study were observation and documentation. Data analysis technique used was descriptive qualitative.The results showed that there was an increase in the ability to recognize the symbols of number through playdough media in the children of group A TK WijayaKusumah / Kartika XIX-26 Tawang Tasikmalaya. This was indicated by the increase of observation result of cycle I, cycle II, and cycle III. Prior to the implementation of the act, the child's ability to recognize the number symbol on the criteria developed very well is 3 children or with an average percentage of 27.8%. In the implementation of cycle I, the ability of children to recognize the symbol of numbers on the criteria developed very well increased to 4 children or with average percentage of 30.6%. In the implementation of cycle II, the ability of children to recognize the symbol of numbers on the criteria developed very well increased to 8 children or with an average percentage of 63.9%. In the implementation of cycle III, the ability of children to recognize the number symbol on the criteria developed very well increased significantly to 10 children or with an average percentage of 86.1%. Penilitian ini bertujuan untuk meningkatkan kemampuan mengenal lambang bilangan melalui media playdough pada anak kelompok A TK Wijaya Kusumah / Kartika XIX-26 Kecamatan Tawang Kota Tasikmalaya.Penelitian ini merupakan penelitian tindakan kelas menggunakan model Kemmis dan Taggart yang dilaksanakan dalam 3 siklus. Subjek penelitian ini adalah anak kelompok A yang berjumlah 12 anak. Teknik pengumpulan data dalam penelitian ini yaitu observasi dan dokumentasi. Teknik analisis data menggunakan deskriptif kualitatif. Hasil penelitian menunjukkan adanya peningkatan kemampuan mengenal lambang bilangan melalui media playdough pada anak kelompok A TK Wijaya Kusumah / Kartika XIX-26 Kecamatan Tawang Kota Tasikmalaya. Hal ini ditunjukkan dengan adanya peningkatan hasil observasi siklus I, siklus II, dan siklus III. Sebelum dilaksanakan tindakan kemampuan anakmengenal lambing bilangan pada kriteria berkembang sangat baik rata-rata sebanyak 3 anak atau dengan rata-rata presentase 27,8%. Pada pelaksanaan siklus I, kemampuan anak mengenal lambing bilangan pada kriteria berkembang sangat baik meningkat menjadi 4 anakataudengan rata-rata presentase 30,6%. Pada pelaksanaansiklus II, kemampuan anak mengenal lambing bilangan pada kriteria berkembang sangat baik meningkat menjadi 8 anak atau dengan rata-rata presentase 63,9%. Pada pelaksanaan siklus III kemampuan anak mengenal lambing bilangan pada kriteria berkembang sangat baik meningkat signifikan menjadi 10 anak atau dengan rata-rata presentase 86,1%.